Differentiated HIV care in sub-Saharan Africa: a scoping review to inform antiretroviral therapy provision for stable HIV-infected individuals in Kenya. Issue 12 (2nd December 2018) - Hagey, Jill M.; Li, Xuan; Barr-Walker, Jill; Penner, Jeremy; Kadima, Julie; Oyaro, Patrick; Cohen, Craig R.
ABSTRACT: Many gaps in care exist for provision of antiretroviral therapy (ART) in sub-Saharan Africa. Differentiated HIV care tailors provision of ART for patients based on their level of acuity, providing alternatives for where, by whom, and how often care occurs. We conducted a scoping review to assess novel differentiated care models for ART provision for stable HIV-infected adults in sub-Saharan Africa, and how these models can be used to guide differentiated care implementation in Kenya. A systematic search was conducted using PubMed, Embase, Web of Science, Popline, Cochrane Library, and African Index Medicus between January 2006 and January 2017. Grey literature searches and handsearching were also used. We included articles that quantitatively assessed the health, acceptability, and cost-effectiveness of differentiated HIV care. Two reviewers independently performed article screening, data extraction and determination of inclusion for analysis. We included 40 publications involving over 240, 000 participants spanning nine countries in sub-Saharan Africa – 54.4% evaluated clinical outcomes, 23.5% evaluated acceptability outcomes, and 22.1% evaluated cost outcomes. Differentiated care models included: facility fast-track drug refills and appointment spacing, facility or community-based ART groups, community ART distribution points or home-based care, and task-shifting or decentralization of care. Studies suggest that these approaches had similar outcomes in viral load suppression and retention in care and were acceptable alternatives to standard HIV care. No clear results could be inferred for studies investigating task shifting and those reporting cost-effectiveness outcomes. Kenya has started to scale up differentiated care models, but further evaluation, quality improvement and research studies should be performed as different models are rolled out.